Synthetic spoofing speech detection method based on center-symmetric local binary pattern - Jia XU; Zhihua JIAN; Honghui JIN; Chao WU; Lin YOU; Yingxiao WU (Dianxin kexue)
In view of the fact that the local binary pattern (LBP) based speech spoofing detection method has low detection accuracy when detecting synthetic speech, a spoofing speech detection method based on center-symmetric local binary pattern (CSLBP) was proposed.In this method, the spectrogram of the speech signal was obtained through short-time Fourier transform (STFT), and then the texture feature was extracted from the spectrogram using the CSLBP.The random forest classifier was trained by the extracted texture feature to realize the discrimination of genuine and spoofing speech.The CSLBP-based method comprehensively considered the value and position relationship of pixels in the spectrogram so as to contain more texture information, and reduced the feature dimension to 16 beneficial to decrease the amount of computation.Experimental results on the ASVspoof 2019 dataset show that, compared with the LBP-based spoofing detection method, the proposed method reduced the tandem detection cost function (t-DCF) of synthetic spoofing speech by 16.98% and increased the detection speed by 89.73%.